Antibacterial action of synthetic antilipopolysaccharide peptides (SALP) involves neutralization of both membrane‐bound and free toxins. (20th March 2019) - Correa, Wilmar; Heinbockel, Lena; Behrends, Jochen; Kaconis, Yani; Barcena‐Varela, Sergio; Gutsmann, Thomas; Mauss, Karl; Schürholz, Tobias; Schromm, Andra B.; Martinez de Tejada, Guillermo; Brandenburg, Klaus
Abstract : Increasing failure of conventional antibiotics to combat bacterial infections requires the urgent development of new antibacterial drugs; a promising class of new drugs based on antimicrobial peptides. Here, we studied the molecular interaction of polycationic synthetic antilipopolysaccharide peptides (SALPs) with various gram‐negative and gram‐positive bacteria, including resistant strains. The analysis of antimicrobial activity by conventional techniques and atomic force microscopy showed a strict dependence on amino acid (aa) sequences, with the type of amino acid, its position within the primary structure, and the sequence length being critical parameters. By monitoring lipopolysaccharide (LPS)‐ or bacteria‐induced cytokine production in human mononuclear cells and whole blood, we found a direct link between the binding of the lead compound Pep19‐2.5 to Salmonella enterica and the anti‐inflammatory activity of the peptide. Thermodynamic analysis of Pep19‐2.5 binding to the bacterial cell envelope showed an exothermic reaction with saturation characteristics, whereas small‐angle X‐ray scattering data indicated a direct attachment of Pep19‐2.5 to the bacterial cell envelope. This binding preferentially takes place to the LPS outer monolayer, as evidenced by the change in the LPS acyl chain and phosphate vibrational bands seen by Fourier‐transform infrared spectroscopy. We report here that the anti‐inflammatory activity of Pep19‐2.5 is not only connected with neutralization of cell‐free bacterial toxins but also with a direct binding of the peptide to the outer leaflet of the bacterial outer membrane. Abstract : Antimicrobial peptides are a promising new class of drugs to combat bacterial infections. The antimicrobial peptide Pep19‐2.5 leads to an agglomeration of bacteria (as shown in the atomic force micrograph) due to bridging via binding to the toxins. The antibacterial action is connected with an anti‐inflammatory effect through the neutralization of the bacterial toxin (lipopolysaccharide), which is the prerequisite for therapeutical efficiency of the peptide.